Deep-coverage study of NB-IoT in different network schemes - Xu-yang ZHANG; Shi-guang LI; Jun ZHOU; Jian-hui MA; Ke-qing LIU (物联网学报)
Deep-coverage enhancement is one of the most important features of NB-IoT network,which allows NB-IoT network meets a large number of application scenarios.This thesis presents the research of NB-IoT deep-coverage enhancement principle,and the performance of two current mainstream network schemes are tested,verified and analyzed.